Participatory Culture of Arctic Monkeys’ Fandom in Indonesia Through Instagram - I. Nabila, Dethisa; Lukmantoro, Triyono; Hasfi, Nurul (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2024)
Drawing on theories of participatory culture, social identity, and new media, the study investigates how fans interact and express themselves in this digital context. This qualitative study employs a textual analysis approach, to examine the comments left by followers on the Instagram feed posts of the @arcticmonkeysindonesia account. The research delves into the rich data obtained through comment extraction, exploring the variety of perspectives and narratives woven within the online fan community. The research findings suggest that Instagram is a key platform for Arctic Monkeys fans in Indonesia to engage with the band, each other, and the broader fan community. Fans use Instagram to share and discuss music, news, and personal experiences, as well as to create and share fan art, memes, and other creative content. This participatory culture provides fans with a space to connect with others who share their love of the band, express their own identities, and build community.